Analysis of Public Debt Sustainability in Middle-Income Arab Countries Post-COVID-19 Pandemic: Early Warning Indicators and Management Scenarios - Ahlaam Aboulgasim Ali Ahmoudah (Journal of Scientific and Human Dimensions, 2026)
This research paper aims to analyze public debt sustainability in middle-income Arab countries following the COVID-19 pandemic, while developing a quantitative predictive model to assess sustainability risks. The study relied on the theoretical framework of optimal debt theory and the International Monetary Fund’s debt sustainability criteria, applying a quantitative analytical methodology to data from 10 middle-income Arab countries for the period 2015-2023. The results showed a significant deterioration in debt sustainability indicators in most of the concerned countries, with the average debt-to-GDP ratio increasing by 15 percentage points since the beginning of the pandemic. An early warning model based on logistic regression was developed, identifying three key predictive indicators for sustainability crises: the debt service-to-revenue ratio, the current account deficit, and the real growth rate. The study proposes four management scenarios ranging from gradual fiscal correction to comprehensive restructuring, emphasizing the necessity of adopting integrated strategies that promote economic growth and improve the efficiency of public spending.